2018
DOI: 10.1371/journal.pone.0191026
|View full text |Cite
|
Sign up to set email alerts
|

Light alcohol consumption has the potential to suppress hepatocellular injury and liver fibrosis in non-alcoholic fatty liver disease

Abstract: Background & aimsThe modest consumption of alcohol has been reported to decrease the incidence of fatty liver or prevalence of steatohepatitis. In this study, we investigated the effect of light alcohol consumption on liver function and gene expression in patients with non-alcoholic fatty liver disease (NAFLD).MethodsThe study group was formed of 178 patients diagnosed with non-alcoholic fatty liver disease, subclassified into two groups for analysis based on the daily alcohol consumption: non-alcohol group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…Long‐term heavy drinking can cause alcoholic liver disease with or without NAFLD. An increasing number of clinical studies have shown that chronic moderate alcohol consumption produces beneficial effects on the low incidence of fatty liver in population and improvement of NAFLD in histology . These results need to be proven in murine models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term heavy drinking can cause alcoholic liver disease with or without NAFLD. An increasing number of clinical studies have shown that chronic moderate alcohol consumption produces beneficial effects on the low incidence of fatty liver in population and improvement of NAFLD in histology . These results need to be proven in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon found that regular alcohol consumption over the course of a lifetime compared to minimal intake appears to have a protective effect on the histological severity of liver disease among patients with NAFLD . Similarly, Yamada et al found that the ballooning and fibrosis scores were significantly lower in NAFLD patients with light alcohol consumption (≤ 20 g of ethanol/d) than in non‐alcohol patients …”
Section: Introductionmentioning
confidence: 97%
“…In a previous large cohort study, wine consumption up to 10 g/day reduced the risk of hepatic steatosis by 50% . A case‐control study examining histology and gene array also found that low‐level alcohol may suppress gene expression involved in the immune response that drives steatohepatitis . Given the small numbers of patients in the current study reporting low‐level wine consumption, it was likely underpowered to assess benefit.…”
mentioning
confidence: 79%
“…Based on this previous work, gene expression profiles in lymphoma cells and the corresponding normal donor PBLs were detected in the present study by high-throughput whole genome expression microarray. Differential expressed genes were analyzed using SAM [14], BRB [15] and LIMMA [16], which identified a total of 202 significantly differentially expressed genes, comprising 44 up-regulated genes and 158 down-regulated genes in the EBV-induced lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Differential gene expression was determined using three methods, namely significance analysis of microarrays (SAM) [14], Biometric Research Program (BRB) [15], and Linear Models for Microarray and RNA-Seq analysis (LIMMA) [16], to ensure that the genes were significantly differentially expressed (differential expression indicated by all three methods). The threshold value for all three methods was set at 2fold change and a false discovery rate of <0.001.…”
Section: Gene Expression Microarray Detection and Analysismentioning
confidence: 99%